Vietnam: country of multiple traditions and regional cuisines (2015)
This article aims to present basic information about Vietnamese food and how it has been highly influenced by the geographical conditions of Vietnam and other countries such as France, China, India. The richness of this cuisine, its ingredients and how was the process of introduction and adaptation by the Vietnamese cuisine of culinary techniques, ingredients and instruments of other countries. Finally, an invitation is made to try and discover more this type of food that has gradually gained worldwide fame.